A study on the comparative growth performance of three genotypes of ducklings with or without supplementary feeding in coastal areas of Bangladesh (Bangladesh Journal of Livestock Research, 2020)
An experiment was conducted with Muscovy, Pekin and Desi white ducklings for a period of 98 days in three villages of Noakhali district in order to know the effect of feed supplementation on growth performance and cost of production under scavenging system of rearing. A factorial experiment (2×3) was designed for 2 feeding regimes (control and supplemented) and 3 genotypes of duck. The feed supplements consisting of a mixture of rice polish, broken rice and wheat bran @ 50, 30 and 20% respectively. At 98 days of age, final live weight, live weight gain, feed conversion efficiency and survivability were highest in Muscovy and lowest in Desi white irrespective of feeding regimes. The differences among the genotypes were statistically significant (P